Use of factorial design with significant interaction and Tukey's Test in agricultural and environmental experiments - Yamada, Jose Tadao; Viana, Rafaela Simoes Espirito; Santos, Ramona Rodrigues; Carvalho, Cleginaldo Pereira de [UNESP]; Almeida, Maria da Gloria Diniz de; Barros, Jose Glenio Medeiros de; Sampaio, Nilo Antonio de Souza (Sindicato Secretarias Estado Sao Paulo, 2023)
This study aimed to present one of the applications of complete factorial planning with significant interactions as well as Tukey's Test in the agricultural and environmental area. Toachieve this objective, applied research of exploratory nature and quantitative approach was carried out. As method and technical procedures were adopted, respectively, the bibliographical research, the literature review, and a case study. As a contribution of this research, it is pointed out the use of this tool in other research fields, but mainly in the environmental area.
Keywords: Statistical Software; Complete Factorial Planning; Tukey's Test